Analisis Besi dalam Ekosistem Lamun dan Hubungannya dengan Sifat Fisikokimia Perairan Pantai Kabupaten Donggala - Tahril, Tahril; Taba, Paulina; Nafie, Nursiah La; Noor, Alfian (Jurnal Natur Indonesia, 2011)
The objectives of the study are to describe the iron content of seagrass area ecosystem and its relation with nature of physico-chemical territorial water. The sampling of seagrass was conducted in purposive sampling technique for every status of the field and performed in three spots of the seagrass ecosystem region with reference to the depth of water and the current direction. Based on statistical tests of factorial and variance analysis indicate that the quality of physico-chemical territorial water in the coastal region of Donggala regency still very good, relatively. The result also showed, The Demand Oxygen and the turbidity gave a positive effect to Fe- seagrass improvement in its various association. Besides, the limiting factor for the low of Fe-seagrass is the height of salinity and water temperature. If the results were combined with another micro and macro mineral analysis will to become the basic for estimating the status of seagrass fertility.